Quasi-Monte Carlo Methods in Stochastic Simulations: An Application to Fiscal Policy Simulations using an Aggregate Disequilibrium Model of the West German Economy - Wolfgang Franz; Klaus Göggelmann; Martin Schellhorn; Peter Winker (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1998)
Different stochastic simulation methods are used in order to check the robustness of the outcome of policy simulations with a macroeconometric model. A macroeconometric disequilibriummodel of the West German economy is used to analyze a reform proposal for the tax system. The model was estimated with quarterly data for the period 1960 to 1994, the presently possible margin. Because of nonlinearities confidence intervals for the simulation results have to be obtained by means of stochastic simulations. The main contribution of this paper consists in presenting the simulation results. The robustness of these results is analyzed using different approaches to stochastic simulation. In particular, different methods for the generation of uniform error terms and their conversion to normal variates are applied. These methods include standard approaches as well as quasi - Monte Carlo methods.
Keywords: 330; policy simulation; macroeconometric disequilibrium model; stochastic simulation; random number generation; quasi - Monte Carlo methods; Ökonometrisches Makromodell; Ungleichgewichtstheorie; Simulation; Steuerreform; Sozialversicherungsfinanzierung; Wirtschaftspolitische Wirkungsanalyse; Deutschland